2019
DOI: 10.35675/befdergi.487409
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Self-Regulated Learning Inventory for Primary School Fourth Grade Students: Validity and Reliability Study

Abstract: Bu araştırma, birinci yazarın ikinci ve üçüncü yazarlar danışmanlığında Marmara Üniversitesi Eğitim Bilimleri Enstitüsü'nde hazırladığı doktora tezinden üretilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Although there are different definitions of self‐regulation in the literature, Zimmerman's (1998) circular model of self‐regulation forms the conceptual basis of the current study (Figure 1). Self‐regulation is not only a process in which personal characteristics are effective but also a cyclical process that includes environmental and behavioral components (Cokcaliskan, 2019; Zimmerman, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are different definitions of self‐regulation in the literature, Zimmerman's (1998) circular model of self‐regulation forms the conceptual basis of the current study (Figure 1). Self‐regulation is not only a process in which personal characteristics are effective but also a cyclical process that includes environmental and behavioral components (Cokcaliskan, 2019; Zimmerman, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are many studies on the development of self‐regulation skills in the literature (Fouche, 2013; Guler & Sahin, 2015; Mataka, 2014; Sun, 2015). Cokcaliskan (2019) concluded that as a result of self‐regulated science teaching practices in primary school fourth‐grade students, there were significant positive changes in students' scientific process skills, science achievement levels, and permanence of knowledge. Ergen and Kanadli (2017) determined that there is a high common effect size between self‐regulation and academic achievement, according to the results of 21 studies they examined.…”
Section: Introductionmentioning
confidence: 99%